Curso Aristotélico Jesuíta Conimbricense. Tomo I: Comentários aos 'Parva Naturalia' - Bernardino Fernando da Costa Marques (Portugaliae Monumenta Neolatina, 2020)
Under the title 'Parva Naturalia' this Aristotelian text knew an unusual international diffusion; among all the Commentaries on the 'Parva Naturalia' stands the Coimbra Commentary (16th Century), written by Manuel de Góis, as a part of the widely known Jesuit Coimbra Commentaries. Indeed, they soon spread throughout European Universities and Colleges and even arrived to South American territories, as well as China, thanks to its several Chinese translations or adaptations published as soon as the 17th Century